RANCANG BANGUN ALAT PENGENDALI LAMPU JARAK JAUH BERBASIS RADIO FREKUENSI 315MHZ FS1000A - Aufa Maulida Fitrianingrum; Mikrajuddin Abdullah (PROSIDING SNAST, 2018)
Control the switching of lamp is one of remote control application that can very useful for household appliance. The main purpose of this research was to make a device that can lighten the human workload. This research developed a remote control using radio frequency technology. This device principle used the principle of wireless system, which the lamp can be turned on or off without using cables. The remote control constructed by radio frequency 315MHz FS1000A module as transmitter and receiver, HT12E and HT12D for connecting the module, and antenna for transferring the signal. To obtain the aim of this research the transmitter will send a signal to the receiver when the switch is pressed. The receiver will receive and process the signal to turn on or off the lamp. Based on the experimental results, this designed device was tested and it was capable to turn on the lights with a range of about 25 meters without obstacles and about 10 meters if there was obstacles. The utilization of this remote control is expected to be developed further and it can be used as an alternative to make human activity more effectively and efficiently, not only for lamp but also for other appliance.